FABRICATION AND CHARACTERIZATION OF CHITOSAN-COATED-POLYVINYL ALCOHOL COMPOSITE FILM - Quejano, Eymard; Duenas, Paul; Alcayaga, Armani; Liberato, Astrid Ayla E. (Philippine Engineering Journal, 2013)
Innovations in engineering ought to address current environmental issues brought by several industries. Among the leading fields producing much plastic wastes is the food-packaging industry. This study used starch-based polymers to try and solve the problem. To produce films, the researchers mixed starch and polyvinyl alcohol, two natural biodegradable polymers, using solution casting. Chitosan was added to form laminates on the film and improve its antimicrobial properties. UTM results showed 284% increase in the tensile properties of the film. In addition, antimicrobial tests showed that increasing Chitosan concentration decreases the growth of both E. coli and S. typhimurium bacteria. The study also addressed the brittleness issues of starch by adding both PVA and Chitosan layers. Results showed that the Starch-PVA system has a vast potential especially since starch is cheap and abundant. Future academic research may also be devoted to improve the microbial inhibition capability of these films.